State and prospects for environmental safety of cutting fluids: Review of technological processing processes - Pogrebnaya Irina; Mikhailova Svetlana (E3S Web of Conferences)
Purpose of the study: to consider technological processes for processing cutting fluids. Scientific hypothesis: it is necessary to change and improve the technological processes themselves in order to comprehensively and most fully process raw materials during the production process, thereby reducing the volume of waste, converting them into forms that are least harmful to the environment. Industry has a significant negative impact on the environment, characterized by the release of hazardous substances and the accumulation of both liquid and solid toxic waste. The need to protect the environment leads to significant changes in general approaches to ensuring the environmental efficiency of production and the introduction of systems for integrated processing of raw materials.